A Remark on the Regularity Criterion for the 3D Boussinesq Equations Involving the Pressure Gradient - Zujin Zhang (Abstract and Applied Analysis)
We consider the three-dimensional Boussinesq equations and obtain a regularity criterion involving the pressure gradient in the Morrey-Companato space Mp,q. This extends and improves the result of Gala (Gala 2013) for the Navier-Stokes equations.